PENGEMBANGAN MODEL PEMBELAJARAN MENULIS DESKRIPSI UNTUK SISWA KELAS IV SEKOLAH DASAR - Mohammad Siddik (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
The purpose of the research was to develop learning model of description writing in elementary schools, i.e. planning product, matter product, and evaluation product. This research used development research design with explanation focus, development, and dissemination. Data in the research was taken from student activity and teacher class four in Kauman 1 elementary school of Malang city and elementary school 006 in Sei Kunjang of Samarinda city.The collected data were analysis by using descriptive qualitative and quantitative techniques. The Research found that from element aspect and essay model showed students’ achievement were very good.